Regional Education Hubs – Rhetoric or Reality - Knight, Jane (International Higher Education, 2010)
The recent trend in cross-border education is building education hubs. There are three categories among education hubs. First, the student hub focuses on recruitment of international students. Second, the education and training hub includes invitation of foreign universities to set up branch campuses. Finally, the knowledge and innovation hub encourages foreign universities to set up a research base to collaborate with local institutions for the production and distribution of knowledge and innovation. Further work is needed to analyze these education hubs.